Peningkatan Hasil Belajar IPS melalui Pembelajaran Kooperatif Tipe Think Paire Share di SMPN 2 Saptosari Gunungkidul - Wahyu Purnaminingsih; Esti Setiawati (UM Purwokerto Press, 2022)
This study aims to improve social studies learning outcomes through cooperative learning of the Think Pair Share type for class VIIIC students of SMPN 2 Saptosari, Gunungkidul Regency, in the 2021/2022 academic year. The subjects of this study were 24 students consisting of 10 males and 14 females. This type of research is classroom action research (CAR) with two cycles. Each cycle consists of three meetings, and each session has four stages, namely (1) planning, (2) implementation, (3) observation, and (4) reflection. Data collection techniques used are tests and observations. The data analysis technique used is a quantitative descriptive technique with a percentage. The results showed that the Think-Pair-Share type of cooperative learning improves social studies learning outcomes. Its show: 1) the number of students who completed the pre-cycle of as many as 13 students (54.16%), 2) at the end of the first cycle of students who reached the KKM as many as 17 students (70.83%), and 3) at the end of the second cycle as many as 20 students (83.33%) managed to reach the KKM. Based on the results of data analysis and discussion, it can be concluded that Think Pair Share cooperative learning can improve social studies learning outcomes for class VIIIC SMPN 2 Saptosari, Gunungkidul Regency for the 2021/2022 academic year.